AN AN ANALYSIS OF STUDENT’S TRANSLATION OF ENGLISH PHRASAL VERBS ON NEWS ITEM TEXT INTO INDONESIAN OF THE THIRD SEMESTER STUDENTS OF TIDAR UNIVERSITY IN THE ACADEMIC YEAR 2016/2017 - Widya Nur Rochmah; Dwi Winarsih; Lilia Indriani (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
This study investigates translation method used in student’s translation of English Phrasal Verbs on news item text into Indonesian of third semester students of Tidar. Translation becomes one of the subjects that have to be improved by the third semester students. The students face difficulties due to English and Bahasa Indonesia have differences in some of linguistic aspect and also background knowledge. It was seen when the students translate phrasal verb that commonly used in news item text. The students did not know the appropriate method used to help them translate phrasal verb easily. The objectives of this research are to know translation method used and to know the translation method mostly used in help students translating English phrasal verbs on news item texts. This study applies1` descriptive qualitative research which consists of an explanation of translation method used in translating Phrasal Verbs. The data were collected by note taking in the form of sentences. The results of this research show that there are 67 phrasal verbs in 23 news item text translated by the students. Based on the findings, it can be concluded that the phrasal verb in this news item texts mostly translated with Faithful Translation Method. However, the students could use Communicative Translation Method and Free Translation method to help them easily translate phrasal verb, it is still understandable and the massage successfully delivered. However, using literal translation method is not appropriate to translated phrasal verb, the meaning always out of context because literal translation method used as a pre-translation process.